2015
DOI: 10.1371/journal.pone.0127517
|View full text |Cite|
|
Sign up to set email alerts
|

Secreted Frizzled-Related Protein 4 Inhibits Glioma Stem-Like Cells by Reversing Epithelial to Mesenchymal Transition, Inducing Apoptosis and Decreasing Cancer Stem Cell Properties

Abstract: The Wnt pathway is integrally involved in regulating self-renewal, proliferation, and maintenance of cancer stem cells (CSCs). We explored the effect of the Wnt antagonist, secreted frizzled-related protein 4 (sFRP4), in modulating epithelial to mesenchymal transition (EMT) in CSCs from human glioblastoma cells lines, U87 and U373. sFRP4 chemo-sensitized CSC-enriched cells to the most commonly used anti-glioblastoma drug, temozolomide (TMZ), by the reversal of EMT. Cell movement, colony formation, and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 47 publications
3
38
0
1
Order By: Relevance
“…Among these genes, CDH1 and Notch-1 (Figure 4A) are regarded as the regulators of Wnt/β-catenin and PI3K/Akt signaling pathways, respectively [21,22]. As the two pathways are always activated in glioma cells and GSCs [23,24,25,26], we hypothesize that CDH1 and Nocth-1 could be the direct targets of miR-92a. To test our hypothesis, qRT-PCR and Western blotting assay were applied to measure the relative expression levels of CDH1 and Notch-1 in two cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Among these genes, CDH1 and Notch-1 (Figure 4A) are regarded as the regulators of Wnt/β-catenin and PI3K/Akt signaling pathways, respectively [21,22]. As the two pathways are always activated in glioma cells and GSCs [23,24,25,26], we hypothesize that CDH1 and Nocth-1 could be the direct targets of miR-92a. To test our hypothesis, qRT-PCR and Western blotting assay were applied to measure the relative expression levels of CDH1 and Notch-1 in two cell types.…”
Section: Resultsmentioning
confidence: 99%
“…Three breast cancer cell lines MDA-MB-231, T47D and MCF7 (NCCS, Pune, India) were enriched for bCSCs by growing as mammospheres in growth factor enriched serum-free medium (SFM) as reported previously (Bhuvanalakshmi et al, 2015) in basal medium (DMEM/F-12 + DMEM-HG) with 100 U/mL PenStrep, 2mM GlutaMAX, and containing 20 ng/mL each of epidermal growth factor (EGF), basic fibroblast growth factor (bFGF; R&D Systems), and leukemia inhibitory factor (LIF; Chemicon). All cells were cultured at 37°C in a humid incubator with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%
“…All cells were cultured at 37°C in a humid incubator with 5% CO2. MTT was performed as described previously (Bhuvanalakshmi et al, 2015) using DG (Sigma–Aldrich, St. Louis, MO, USA) at concentrations 0–500 μM. After determining the IC50 value at 400 μM after 24 h, the subsequent experiments were at this concentration of DG for 24 h. BrdU and caspase assays were performed as described previously (Bhuvanalakshmi et al, 2014) with bCSCs from MDA-MB-231 and T47D.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated that silencing SFRP4 inhibited eWAT preadipocyte differentiation; in contrast, SFRP4 silencing promoted iWAT preadipocyte differentiation through the induction of adipocyte differentiation progression. Although SFRP4 has been shown to play an important role in several types of disease [32-34], the expression and function of SFRP4 in eWAT adipocyte development has not been fully investigated. In the current report, we first observed that SFRP4 expression was increased upon the induction of differentiation in eWAT preadipocytes.…”
Section: Discussionmentioning
confidence: 99%